Cosmos, culture and landscape : documenting, learning and sharing Aboriginal astronomical knowledge in contemporary society - Goldsmith, John Martin (Curtin University, 2014)
Contemporary Australian Aboriginal astronomical knowledge, its documentation, sharing and communication is investigated, primarily from three Western Australian locations (1) Murchison region (associated with Murchison Radio-astronomy Observatory), (2) East Kimberley (Wolfe Creek Meteorite Crater) and (3) the South West of Western Australia. Astronomical knowledge is examined via three surveys and in-depth interviews with 27 participants. Digital imaging (360° & timelapse) is applied to create new and original Aboriginal astronomy resources (virtual tour and exhibition videos).